ZIRCONS FROM KIMBERLITE: NEW INSIGHTS FROM OXYGEN ISOTOPES, TRACE ELEMENTS, AND TI IN ZIRCON THERMOMETRY - Page F.Z.; Fu B.; Kita N.T.; Fournelle J.; Spicuzza M.J.; Valley J.W.; Schulze D.J.; Viljoen F.; Basei M.A.S. (My University, 2007)
Zircons found in mantle-sourced kimberlite provide probes into the isotopic chemistry of the asthenosphere and subcontinental lithospheric mantle. However, little is known about the conditions of formation of these zircons. A suite of 88 zircons found in kimberlites from Africa, Siberia, Brazil, and the United States have been analyzed for their Ti concentration and selected zircons were analyzed for their Rare Earth Element (REE) concentrations by ion microprobe. In addition, precise and accurate laser-fluorination oxygen isotope data were obtained for zircons from Brazil (5.1 ± 0.3‰, 1SD) and the Midwest United States (5.3 ± 0.3‰), yielding mantle-like δ18O values similar to published data for Africa (5.2 ± 0.3‰) and Siberia (5.3 ± 0.2‰). Most megacrysts in this study preserve fine-scale, oscillatory zoning in CL and are generally homogenous in oxygen isotopic composition, consistent with preservation of primary compositions. A few zircons from Brazil show some evidence of chemical zoning due to recrystallization. The Ti content of mantle zircon is in general low with average compositions from each locality of 13 ± 8.4 ppm (1SD, Kaapvaal craton), 12 ± 8.7 ppm (Siberian platform), 18 ± 11 ppm (Brazil), and 4.8 ±4.3 ppm (United States). The recently calibrated Ti in zircon thermometer yields an average temperature of 744 ±62 °C (1SD) for the average of 13 ± 9 ppm Ti, with no correction for pressure, aTiO2, or aSiO2. The Ti content of zircons found within rutile nodules from the Orapa kimberlite (Kaapvaal craton) is almost indistinguishable from those with no constraint on aTiO2, suggesting that reduced aTiO2 is not responsible for lower than expected mantle temperatures. The average temperature in this study corresponds to ~3 GPa on a 40 mW/m2 cratonic geotherm. If correct, this would suggest that zircon megacrysts from all four cratons formed in the shallow lithospheric mantle. However, there are several possibly confounding effects to this thermometer, including: a pressure correction and disequilibrium zircon growth. Zircons from rutile nodules have REE contents that span the range of mantle zircon REE and are similar to both zircon megacrysts and zircons from metasomatic assemblages. © 2007 Elsevier Ltd. All rights reserved.